Acute Tubular Necrosis Following Interferon-Based Therapy for Hepatitis C: Case Study with Literature Review - Fabrizio Fabrizi; Alessio Aghemo; G. Battista Fogazzi; Gabriella Moroni; Patrizia Passerini; Roberta D'Ambrosio; Piergiorgio Messa (Karger Publishers, 2014)
Background/Aims: Interferon treatment of malignant or viral diseases can be accompanied by various side-effects including nephro-toxicity. Methods: We report on a 68-year-old Caucasian male who received dual therapy with pegylated interferon 2a plus ribavirin for chronic hepatitis C. Results: After three months of antiviral therapy, the patient developed acute kidney failure (serum creatinine up to 6 mg/dL) with mild proteinuria (500 mg daily) and haematuria. Immediate immunosuppressive therapy with high-dose intravenous steroids did not improve kidney function. Kidney biopsy was consistent with acute tubular necrosis without glomerular abnormalities. He started long-term peritoneal dialysis (four regular exchanges) to provide both dialysis adequacy and ascites removal. Kidney function gradually improved over the following months (serum creatinine around 2 mg/dL) and peritoneal dialysis was continued with two exchanges daily. The temporal relationship between the administration of the drug and the occurrence of nephro-toxicity, and the absence of other obvious reasons for acute tubular necrosis support a causative role for pegylated interferon; benefit on kidney disease was noted after withdrawal of antiviral agents. An extensive review of the literature on acute tubular necrosis associated with interferon-based therapy, based on in vitro data and earlier case-reports, has been made. The proposed pathogenic mechanisms are reviewed. Conclusions: Our case emphasizes the importance of monitoring renal function during treatment of chronic hepatitis C with antiviral combination therapy as treatment may precipitate kidney damage at tubular level.